Molecular taxonomy and subgeneric classification of tapeworms of the genus moniezia blanchard, 1891 (Cestoda, Anoplocephlidae) in nothern cervids (Alces and Rangifer) - Chilton, Neil B.; O’Callaghan, Michael G.; Beveridge, Ian; Andrews, Ross H. (Springer Verlag, 2007)
Multilocus enzyme electrophoresis (MEE) was used to genetically compare Moniezia spp. collected from sheep and cattle in southern Australia. Fifteen enzyme loci were established for the genetic characterisation of individual specimens of Moniezia, which represents a significant increase in the number of loci that was previously available for these cestodes. Another four enzyme loci were also identified as providing potential genetic markers. There were no differences in staining activity or banding patterns of different body regions of individual cestodes. Fixed genetic differences between Moniezia expansa and Moniezia benedeni were detected at 10 (77%) loci. Individuals that lacked the diagnostic morphological characters (i.e. the arrangement pattern of the interproglottidal glands) could be assigned to either morphospecies based on their MEE profiles. Genetic differences were also detected among individuals of the two morphospecies. One specimen of M. expansa had fixed genetic differences at 33% of enzyme loci when compared to all other specimens of M. expansa. Fixed genetic differences were also detected between the two groups of M. benedeni at 12 of 13 (92%) enzyme loci. This magnitude of genetic difference was greater than that detected between the two morphospecies. This provides evidence for the existence of cryptic species in the genus Moniezia. Int
Parasitol Research (2007) 100:1187–1192 DOI 10.1007/s00436-006-0388-4
Keywords: Multilocus; Enzyme electrophoresis; Moniezia; Bestatin